Мултирезидуална анализа на антибиотици во млеко со примена на LC-MS/MS метод - Ѓулаи, Алија (Факултет за ветеринарна медицина, УКИМ, Скопје, 2021)
Antibiotics are used in domestic animals to treat and prevent certain diseases, and in some cases are used as growth promoters because they improve the efficiency and utilization of food. Inadequate use and application of these drugs can result in the presence of their residues in milk, meat, eggs and internal organs. The effects of antibiotic residues in food of animal origin can seriously affect human health which can result in allergic reactions, resistance to pathogenic microorganisms, disruption of the normal microflora in the body, carcinogenic impact, and in addition to the dairy industry inhibit bacterial fermentation and adversely affect the quality of the final product. Due to all the previously mentioned side effects, it is necessary to constantly monitor and control the presence of antibiotics in food of animal origin in order to place on the market the food that maintains them. To this purpose, it is necessary to develop appropriate precise, accurate, selective and sensitive analytical methods for detection of these substances. The aim of this dissertation was to develop an LC-MS / MS method for the detection of multi-class antibiotics in raw milk. In the study were optimized the chromatographic conditions, the conditions of the mass detector, the extraction method, after that the method was validated, and a routine analysis of 400 samples of raw milk was also performed. From the obtained results it can be concluded that the method is suitable for the analysis of 23 antibiotics in raw milk. The method is accurate, precise, selective and specific, which can be concluded from the validation parameters: linearity, selectivity / specificity, LOD, LOQ, CCα, CCβ, accuracy and precision which are in accordance with the criteria prescribed in the Commission Decision 2002 / 657 / EC. A total of 400 raw milk samples were tested. Antibiotics were detected in 21 samples (5.25%). Antibiotic concentrations were within the permitted MRLs, meaning that none of the samples contained an antibiotic above the prescribed value. As a result of the above we can conclude that the method can be used in routine analysis, and the control of milk, as well as other foods of animal origin must be constant, in order to protect public health.
Multi-residual analysis of antibiotics in milk using LC-MS/MS method
Докторска дисертација одбранета во 2021 година на Факултетот за ветеринарна медицина во Скопје, под менторство на проф. д–р Зехра Хајрулаи Муслиу.
Keywords: antibiotics, raw milk, optimization, validation, LC-MS / MS